(untitled) (Research, Society and Development, 2021)
Objective: To review the literature systematically in relation to the effectiveness of the adhesive for dental prostheses presented in terms of patient satisfaction and to evaluate the differences regarding the use or not of them. Methodology: A search was carried out in the databases PubMed / MEDLINE, Embase, Scopus and Web of Science according to the criteria of Preferred Reports for Systematic Reviews and Meta-Analysis. The PICO question was used to address the following specific question: "Patients who use adhesives on full denture satisfaction?". Results: Sixteen studies with a total of 1133 patients with age average of 67 years were included; in relation to masticatory capacity, improvement was found in feeding, increased vertical movement in the mandible and less intrusion of the prosthesis. As for satisfaction, studies have shown greater comfort, improvement in social, psychological, quality of life and oral health and self-confidence. No serious side effects have been reported and only oral adverse events have been coded. Conclusion: Although adhesives for dental prostheses do not improve their function, that is, they are not capable of problems related to anatomy or errors in the manufacture of the prosthesis, they affect as subjective evaluations of patients. The use of adhesives for prolonged complete dentures increases their retention and stability and positively affects the patient’s satisfaction with regard to masticatory capacity, comfort and confidence, provided the recovery is adequate.